x/2-(2x+1)/6=(x+1)/3

Simple and best practice solution for x/2-(2x+1)/6=(x+1)/3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x/2-(2x+1)/6=(x+1)/3 equation:


x/2-(2x+1)/6=(x+1)/3

We simplify the equation to the form, which is simple to understand
x/2-(2x+1)/6=(x+1)/3

Simplifying:
+ 0.5x-(2x+1)/6=(x+1)/3

Reorder the terms in parentheses
+ 0.5x-( + 0.333333333333x + 0.166666666667)=(x+1)/3

Remove unnecessary parentheses
+ 0.5x-0.333333333333x-0.166666666667=(x+1)/3

Reorder the terms in parentheses
+ 0.5x-0.333333333333x-0.166666666667=( + 0.333333333333x + 0.333333333333)

Remove unnecessary parentheses
+ 0.5x-0.333333333333x-0.166666666667=0.333333333333x + 0.333333333333

We move all terms containing x to the left and all other terms to the right.
+ 0.5x-0.333333333333x-0.333333333333x=0.333333333333 + 0.166666666667

We simplify left and right side of the equation.
-0.166666666666x=0.5

We divide both sides of the equation by -0.166666666666 to get x.
x=-3.00000000001

See similar equations:

| 8(u-8)=-5lu-38k | | x(21-2x)(39-2x)= | | -10z^2+11z=3 | | 5t-(t-2)=2-3.(t-5) | | 71-6x=39x+21 | | 13-8x=173-36x | | 5x^2+8=2x | | 7(t+4)+3(2t-5)= | | 19-y=x-x | | 7(q+2)=7q+14 | | 2x+4x=21 | | =8+8 | | 2x=62 | | x+2(y-x)=5+x | | 4x+27=191 | | 5r^2-39r-8=0 | | -15=-7y+4(y+3) | | 5(29-5x)=x-112 | | -2u+5=9-3u | | 2x+17=74 | | 3x-24+5x=7x+24 | | 12x+3y=y+9 | | 2(3y+4)=4-3 | | 0.5(4x-10)=x+15 | | 66-5x=31x+18 | | 6x+7.1=20.3 | | 2x+12=380 | | x(5x+30)=0 | | 11-10x=147-38x | | 7x+4=9x+13 | | p^2+16p=-15 | | 8(4d-6)= |

Equations solver categories